Antibiotics in the agricultural soils from the Yangtze River Delta, China. (December 2017) - Sun, Jianteng; Zeng, Qingtao; Tsang, Daniel C.W.; Zhu, L.Z.; Li, X.D.
Abstract: This study focused on the occurrence and spatial distribution of 13 common antibiotics in the agricultural soils of the Yangtze River Delta (YRD), China. Antibiotics were detected in all the 241 soil samples ( i.e., 100% detection rate) with the total concentrations ranging from 4.55 to 2, 010 ng/g dry weight. The concentrations of three antibiotic classes decreased in the order: quinolones (mean 48.8 ng/g) > tetracyclines (mean 34.9 ng/g) > sulfonamides (mean 2.35 ng/g). Ciprofloxacin was the prevalent compound with a mean concentration of 27.7 ng/g, followed by oxytetracycline (mean of 18.9 ng/g). A distinct spatial distribution was observed, where high concentrations of antibiotics were detected in the sites adjacent to the livestock and poultry farms. The potential sources of antibiotics in the agricultural soils were the application of manure and wastewater irrigation in this region. Risk assessment for single antibiotic compound indicated that tetracyclines and quinolones could pose a potential risk, in which doxycycline and ciprofloxacin had the most severe ecological effect in the agricultural soils. Antibiotic resistance genes (ARGs), such as tet A, sul I, and qnr S, were detected in 15 analyzed soil samples, and sul I showed significant correlations with quinolones, tetracyclines, copper, and zinc. Further studies on the distribution of other ARGs in agricultural soil at a region-scale are needed for the risk management of extensively used antibiotics and major ARGs. Graphical abstract: Highlights: Antibiotic residuals were widely detected in agricultural soils from the YRD region of China. Higher concentrations of antibiotics were found in Jiangsu and Shanghai. Manure application and wastewater irrigation were the main sources of antibiotic inputs. The ARGs tet A, sul I, and qnr S were detected in the agricultural soils.